Current perspectives and trends of CD39-CD73-eAdo/A2aR research in tumor microenvironment: a bibliometric analysis - Huang, Tian; Ren, Xiangqing; Tang, Xiaolong; Wang, Yuping; Ji, Rui; Guo, Qinghong; Ma, Qian; Zheng, Ya; Hu, Zenan; Zhou, Yongning (Frontiers in Immunology, 2024)
Background and Objective: This study summarizes and explores the research trends and hotspots of the adenosine axis in the field of TME to provide ideas for further in-depth research. Methods: Literature information was obtained from the Web of Science core collection database. The VOS viewer and the bibliometric tool based on R were used to quantify and identify the distribution of author keywords and the co-occurrence of author keywords, highly cited articles, and highly co-cited references of CD39-CD73-eAdo/A2aR in the field of TME were analyzed to determine research hotspots and trends. Result: 1,721 articles published in the past ten years were included in this study. Through bibliometric analysis, we found that (1) 69 countries and regions explored the effect of the CD39-CD73-eAdo/A2aR on TME, and the research was generally on the rise. (2) Harvard University has published the most articles in this field. (3) 12,065 authors contributed to the publication of papers in this field, of which 23 published at least eight papers. (4) 579 scholarly journals have published articles in this field. The journal FRONTIERS IN IMMUNOLOGY published the most significant number of papers. (5) “The ectonucleotidases CD39 and CD73: Novel checkpoint inhibitor targets” was the most frequently cited article (573 times). (6) Through the analysis of author keywords, we found that the relationship between adenosine and immunotherapy is a core concept for many researchers in this field. Immunotherapy, immunosuppression, immune checkpoint, and immune checkpoint inhibitors were the hot keywords in the research, reflecting the importance of the adenosine metabolic pathway in tumor immunotherapy. The keywords such as Immunogenic cell death, T cells, Sting, regulatory T cells, innate immunity, and immune infiltration demonstrated the pathways by which adenosine affected the TME. Conclusion: The effect of CD39-CD73-eAdo/A2aR on the infiltration and function of various immune cells in TME, tumor immunotherapy response, and patient prognosis has attracted the attention of researchers from many countries/regions. Further exploration of targeted inhibition of CD39-CD73-eAdo/A2aR alone or in combination with other immunotherapy, radiotherapy, and chemotherapy in treating various cancer types and developing effective clinical therapeutic drugs are continuous research hotspots in this field.